Advanced Strategies to Preserve Quality and Extend Shelf Life of Foods (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book includes recent research activities in the field of food quality assurance and shelf-life extension. The goal is to broaden our current knowledge of advanced approaches to guaranteeing the maintenance of the properties of packaged products during storage. Preservation strategies based on vacuum packaging, innovative active packaging, emerging technologies, and horticultural by-products are widely discussed in specific chapters. Taken together, these research studies constitute clear evidence that achieving food shelf-life extension is still a complex and multifaceted process. The book reflects advances made in the field and, with the addition of a chapter also covering the secondary shelf-life topic, it will provide the latest research for academics working in the field of novel processing, antimicrobial/antioxidant substances, by-product recycling and active packaging. The research collected in this book is ideal for those working in the food quality industry.